Deconstructing tolerance with clobazam: Post hoc analyses from an open-label extension study. (25th October 2016) - Gidal, Barry E.; Wechsler, Robert T.; Sankar, Raman; Montouris, Georgia D.; White, H. Steve; Cloyd, James C.; Kane, Mary Clare; Peng, Guangbin; Tworek, David M.; Shen, Vivienne; Isojarvi, Jouko
Abstract : Objective: To evaluate potential development of tolerance to adjunctive clobazam in patients with Lennox-Gastaut syndrome. Methods: Eligible patients enrolled in open-label extension study OV-1004, which continued until clobazam was commercially available in the United States or for a maximum of 2 years outside the United States. Enrolled patients started at 0.5 mg·kg −1 ·d −1 clobazam, not to exceed 40 mg/d. After 48 hours, dosages could be adjusted up to 2.0 mg·kg −1 ·d −1 (maximum 80 mg/d) on the basis of efficacy and tolerability. Post hoc analyses evaluated mean dosages and drop-seizure rates for the first 2 years of the open-label extension based on responder categories and baseline seizure quartiles in OV-1012. Individual patient listings were reviewed for dosage increases ≥40% and increasing seizure rates. Results: Data from 200 patients were included. For patients free of drop seizures, there was no notable change in dosage over 24 months. For responder groups still exhibiting drop seizures, dosages were increased. Weekly drop-seizure rates for 100% and ≥75% responders demonstrated a consistent response over time. Few patients had a dosage increase ≥40% associated with an increase in seizure rates. Conclusions: Two-year findings suggest that the majority of patients do not develop tolerance to the antiseizure actions of clobazam. Observed dosage increases may reflect best efforts to achieve seizure freedom. It is possible that the clinical development of tolerance to clobazam has been overstated. ClinicalTrials.gov identifier: NCT00518713 and NCT01160770. Classification of evidence: This study provides Class III evidence that the majority of patients do not develop tolerance to clobazam over 2 years of treatment.